Investigating the Interactive Effect of Tax Risk and Social Responsibility on the Value of Companies Accepted in Tehran Stock Exchange - Jamal Barzegari Khanaghah (Ph.D) (Shahid Bahonar University of Kerman, 2020)
Objective: The aim of this study was to provide a model for tax risk measurment in the first step, and to examine the impact of tax risk and social responsibility as well as their interactive effect on the value of companies accepted in the Iranian capital market in single-, three-, four- and five-factor pricing models, in the next step. Another aim was to compare the explanatory power of the models of capital asset pricing. Methods: In this study, the data of 103 companies listed in the Tehran Stock Exchange, TSE, during the years 2011-2017 were collected, and then, analyzed using panel data estimation model. This research is an applied and analytical-explanatory one. Results: The research findings showed that tax risk and social responsibility have significant effects on the value of the company in all four capital asset pricing models in the companies in the TSE. Conclusion: The effect of tax risk on company value is an opposite effect, the impact of social responsibility on company value is a direct effect, but the interactive effect of tax risk and social responsibility on company value is not significant. Comparing the models, it is shown that the five-factor model explains the relationship between these variables in the Iranian capital market better than other models.